Riboflavin and pantothenic acid biosynthesis are crucial for iron homeostasis and virulence in the pathogenic mold Aspergillus fumigatus. Issue 1 (31st December 2018) - Dietl, Anna-Maria; Meir, Zohar; Shadkchan, Yona; Osherov, Nir; Haas, Hubertus
ABSTRACT: Background : Aspergillus fumigatus is the most prevalent airborne fungal pathogen, causing invasive fungal infections mainly in immunosuppressed individuals. Death rates from invasive aspergillosis remain high because of limited treatment options and increasing antifungal resistance. The aim of this study was to identify key fungal-specific genes participating in vitamin B biosynthesis in A. fumigatus . Because these genes are absent in humans they can serve as possible novel targets for antifungal drug development.Methods : By sequence homology we identified, deleted and analysed four key A. fumigatus genes (riboB, panA, pyroA, thiB) involved respectively in the biosynthesis of riboflavin (vitamin B2), pantothenic acid (vitamin B5), pyridoxine (vitamin B6) and thiamine (vitamin B1).Results : Deletion of riboB, panA, pyroA or thiB resulted in respective vitamin auxotrophy. Lack of riboflavin and pantothenic acid biosynthesis perturbed many cellular processes including iron homeostasis. Virulence in murine pulmonary and systemic models of infection was severely attenuated following deletion of riboB and panA, strongly reduced after pyroA deletion and weakly attenuated after thiB deletion.Conclusions : This study reveals the biosynthetic pathways of the vitamins riboflavin and pantothenic acid as attractive targets for novel antifungal therapy. Moreover, the virulence studies with auxotrophic mutants serve to identify the availability of nutrients to pathogens in host niches. Abbreviations : BPS: bathophenanthrolinedisulfonate; BSA: bovine serum albumin; CFU: colony forming unit; -Fe: iron starvation; +Fe: iron sufficiency; hFe: high iron; NRPSs: nonribosomal peptide synthetases; PKSs: polyketide synthaseses; wt: wild type